2003
DOI: 10.1097/00005110-200309000-00008
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Nurse Staffing and Patient Outcomes

Abstract: The findings of this study add to our understanding of the importance of nurse staffing and its relationship to the patient outcome of hospital mortality. Further, the findings also provide information for hospital and nursing administrators to use when restructuring the clinical workforce, revising hospital policies, or making contractual decisions on behalf of nursing and public beneficiaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
86
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(93 citation statements)
references
References 16 publications
7
86
0
Order By: Relevance
“…A systematic review of research confirming the relationship between low nurse staffing levels and adverse patient outcomes found 101 studies published up to 2006, mainly from the USA (Kane et al, 2007). Major studies have continued to be undertaken in countries around the world including Australia (Twigg et al, 2011), China (You et al, 2013), England (Rafferty et al, 2007), Thailand (Sasichay-Akkadechanunt et al, 2003) and across 12…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of research confirming the relationship between low nurse staffing levels and adverse patient outcomes found 101 studies published up to 2006, mainly from the USA (Kane et al, 2007). Major studies have continued to be undertaken in countries around the world including Australia (Twigg et al, 2011), China (You et al, 2013), England (Rafferty et al, 2007), Thailand (Sasichay-Akkadechanunt et al, 2003) and across 12…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these studies demonstrate the possibility that a hospital with a cohesive multidisciplinary team focused on early diagnosis and treatment of complications has a positive influence on postoperative results [164][165][166] . Additionally, there is evidence that hospitals with higher volume of procedures have lower perioperative mortality than hospitals with lower volume of surgeries, even after adjusting for other variables 167 .…”
Section: Choosing the Hospitalmentioning
confidence: 75%
“…Other studies have already shown lower perioperative mortality in hospitals with more nurses per bed and in ICUs with daily visits of expert intensivists, which reflect effective systems of communication and probably higher probability of prompt recognition of complications [164][165][166] . Thus, these studies demonstrate the possibility that a hospital with a cohesive multidisciplinary team focused on early diagnosis and treatment of complications has a positive influence on postoperative results [164][165][166] .…”
Section: Choosing the Hospitalmentioning
confidence: 85%
“…Two other studies found conflicting results on the influence of RNs' experience on patient mortality. Tourangeau et al 22 reported that for each additional average year of clinical nursing experience, there were 4 to 6 fewer deaths within 30 days among every 1000 acute medical patients discharged, whereas Sasichay-Akkadechanunt and colleagues 23 found no relationship between the number of years of experience as an RN and patient mortality.…”
Section: Nurses' Comments To Study On Nurse Education and Patient Mormentioning
confidence: 99%